To create a table for the reflection about the origin of the function \( f(x) = (x + 2) + 1 \), we first need to evaluate \( f(x) \) at the specified values of \( x = 0, -1, -2 \) and then find \( -f(-x) \) for those corresponding \( x \) values.
Step 1: Calculate \( f(x) \)
- \( f(0) = (0 + 2) + 1 = 2 + 1 = 3 \)
- \( f(-1) = (-1 + 2) + 1 = 1 + 1 = 2 \)
- \( f(-2) = (-2 + 2) + 1 = 0 + 1 = 1 \)
Step 2: Calculate \( -f(-x) \)
Now, we will evaluate \( -f(-x) \):
-
For \( x = 0 \):
- \( -f(-0) = -f(0) = -3 \)
-
For \( x = -1 \):
- \( -f(-(-1)) = -f(1) \)
- \( f(1) = (1 + 2) + 1 = 3 + 1 = 4 \)
- So, \( -f(1) = -4 \)
-
For \( x = -2 \):
- \( -f(-(-2)) = -f(2) \)
- \( f(2) = (2 + 2) + 1 = 4 + 1 = 5 \)
- So, \( -f(2) = -5 \)
Step 3: Create the Table
Now we can summarize the values in a table.
| \( x \) | \( f(x) \) | \( -f(-x) \) | |---------|------------|--------------| | 0 | 3 | -3 | | -1 | 2 | -4 | | -2 | 1 | -5 |
This table shows the function values and their corresponding reflections about the origin.